Supplementation of docosahexaenoic acid (DHA) / Eicosapentaenoic acid (EPA) in a ratio of 1/1.3 during the last trimester of pregnancy results in EPA accumulation in cord blood - BATIREL, SAİME (ELSEVIER SCI LTD, 2017)
Omega-3 fatty acids (n-3 FA), specifically DHA, are associated with fetal growth and development. We aimed to determine the levels of DHA and EPA in cord serum after n-3 FA supplementation during the last trimester of pregnancy. Among 55 women, 23 were administered daily one capsule of n-3 FA supplement, involving DHA/EPA in a ratio of 1/1.3. Twenty nine women were enrolled as control group. Blood samples were collected at 22-24 weeks of gestation and at delivery. Fatty acids were analyzed with the method of GC-MS. Cord DHA level increased and EPA level decreased in both groups between the days of 22-24 and delivery. However, decrease in cord EPA level was significant in control group (p < 0.001) but not in supplement group (p > 0.05). Supplementation of DHA/EPA in a ratio of 1/1.3 during the last trimester of pregnancy caused higher cord EPA level compared to control group indicating an accumulation in umbilical cord.
Keywords: Docosahexaenoic acid (DHA); Eicosapentaenoic acid (EPA); Omega-3 fatty acids; Omega supplement; Pregnancy; Umbilical cord; N-3 FATTY-ACIDS; SERUM-LIPIDS; PLASMA; HEALTH; WOMEN; PROSTAGLANDINS; TRANSPORT; BEHAVIOR; HUMANS; TISSUE